Strategic technology management in technical and technological colleges and its impact on traditional education - Carofilis Hernández , María Alejandra (Revista Minerva, 2023)
This work proposes to analyze how technology has become an indispensable tool when talking about higher education, it will help us to know how it has been implemented little by little, how it has evolved and especially what methods have been used to achieve a good performance and development of educational institutions. The importance of it is to analyze how the Higher Technical and Technological Institutes, only in Ecuador, have gained ground in the choice of a third level career: it is to enter to know the level of competitiveness of these institutions, which have been overshadowed by the universities and have been proposed to improve in order to offer a quality higher education: This is the importance of our research, because we are not only going to discover a strategic plan or a market analysis, we are going to know the challenges and problems of these educational institutions to be able to be at the academic level that students who choose a technical or technological career deserve.